β-enaminocetonas trialometil substituídas: síntese, estrutura e propriedades fotofísicas de quelatos difluororganoboro e reações de ciclocondensação intramoleculares - Rosa, Wilian Carvalho da (2020)
This work shows the synthesis, spectroscopic structural characterization, microbiological properties determination, photophysical, and the DNA bonds of the new difluorooraganoboron compounds, wich are BODIPYs derivatives and analogues synthesized from substituted trihalomethyl β-enaminoketones. Furthermore, also presents a study of intramolecular cyclization reactions and the regioselectivity elucidation of ring closure in derivatives aminocoumarinics. So, were obtained two series of β-enaminoketones wich were used with a precursos, alkyl(aryl)amines (5aa-ai, 5be) (61-90%) and, 6-amino-coumarin (9,10a-e) (50-95%), with the substituted alkyl(aryl) trihalomethyl. These substitued trihalomethyl β-enaminoketones were applied with a precursor bloc in the synthesis of new compounds 2,2,-difluoro-3,4-alkyl(heteroaryl)-6-(trichloromethyl)-2H-1,3,2-oxazaborinin-3- ium-2-uides in front of BF3·OEt2 as a source of BF2. The trifluoromethyled β-aminoketones didn’t presented enough reactivity for the synthesis of difluoroorganoboron compounds. Whereas the trichloromethyl β-aminoketones carried out to a synthesis of thirteen unpublished compounds (7aa-ai, 7be, 12a, 12b, 12e) with good yields (50 – 91%) Some compouds showed antimicrobial effects in front of many pathogenic microorganisms in low concentration, lower that presents cytotoxics effects. In analysis of interaction with DNA through spectroscopical methods of absorption and emission, the derivatives 7aa-i e 7be showed strongs interactions with ct-DNA, apresentaram fortes interações com o ct-DNA, wich are attributed to the hydrophobic forces. For the compounds 12a, 12b, 12e were performed spectrocopic tests of absortion and emission that presentes two absortion bands: the first in the region of 270-290 nm and the second in the region of 305-370 nm. All derivatives coumarinics showed fluorescence with low and moderate quantum yields (Φ) in dichloromethane when compared to the 9,10-diphenylanthracene (DPA), emission reference. The substracts substituted trihalomethyl β-enaminoketones submitted to thermocyclization under acid catalysis didn’t presented regioselectivity. Only the substituted trifluoromethyl β-enaminocoumarin 9b carried to formation of two products one linear (13b) (15%) and another angular (15b) (10%) being that chlorinated didn’t reacted. Finally was observed that chemical behavior of the nucleophile 4 amino-coumarin in front of the substituted trihalomethyl vinylketones under acid catalysis, carried out the pyrido-coumarins (20a-i) directly, without a intermediate formation, the β- enaminoketones. The methodology cariied to the synthesis of nine compounds trifluoromethyled 1,4-substituted in yield between 25 – 66%. The substituted trichloromethyl vinylketones didn’t reacted.